Grit dan Career Adaptability Perawat di Masa Pandemi - Lestari, Angelina Kartini Agung; Sumargi, Agnes Maria; Ngonde, Sylvia Kurniawati (Universitas Ciputra Surabaya, 2022)
Abstract. Nurses have to serve patients intensively, and therefore, they face new challenges and require career adaptability. Career adaptability is the ability to self-regulate in the face of challenges in the work environment in order to solve problems flexibly, and experience career satisfaction and success. One of the factors that promote career adaptability is grit. Grit is an individual’s endurance to pursue an interest and efforts for long-term goals. The purpose of this study was to examine the relationship between grit and career adaptability among nurses during the COVID-19 pandemic. Participants were 48 nurses in Surabaya aged 21 to 39 years old. They completed the Career Adapt-Abilities Scale (CAAS) and 12-Item Grit Scale. Kendall's tau-b correlation test was used for data analysis. Results showed that there was a significant positive relationship between grit and career adaptability Further studies should involve more participants working at hospitals in different regions of Indonesia.